THE INTERACTION OF AZOMETHANE WITH SI(100) - Loh, K; Kingsley, C; Foord, J; Jackman, R (Elsevier, 1995)
The adsorption of azomethane, and azomethane pre-cracked to form methyl and dinitrogen species, on Si(100) has been studied using XPS and thermal desorption techniques. Azomethane adsorbs with appreciable sticking probability at 300 K, most probably producing an adlayer containing a mixture of molecularly adsorbed and partially dissociated species. N = N bond cleavage dominates the partial decomposition process, resulting in the formation and desorption of methylamine and hydrogen cyanide. At adsorption temperatures above 600 K, complete dissociation of the molecule is observed, producing mixed silicon carbide and nitride phases which can be grown efficiently up to film thicknesses in excess of 3 nm. Pre-cracking of the azomethane results in the efficient deposition of methyl species which thermally decompose to produce silicon carbide films. This approach very much reduces the nitrogen content of the surface phases formed due to the low sticking probability of dinitrogen on silicon and silicon carbide surfaces.